PEMBUATAN MESIN PROFIL (ROUTER) STATIS UNTUK INDUSTRI KECIL MEBEL KA YU - Darmono, Darmono (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
The  voucher  program entitled  "Manufacturing  Static  Profiling  Machine(Router) for Small Wood Furniture Industries"  aims to increase  productivity  of the Indah  Jaya wood  furniture  industry especially  in profile  production  of the produced furniture.  It also wants to know the capacity and productivity  of such static router machine.The  steps  of  this  manufacturing  static  router  machine  are  planning,machine manufacturing,  and training for industry partner workers.  The planning step  includes  : (l)   designing  machine  plan  draft,  (2)  calculating  the  needed materials,  and  (3) calculating  the  implementation  cost.  The  machine manufacturing  step  includes  :  (1)  material  cutting  to  fit  the  work  draft,  (2) welding,  (3) assembling,  (4) electric installation. (5) machine performance  test, and (6) painting. The training for industry partner workers consists of:  (1) theory and speech delivery, (2) demonstration of machine using, and (3) mahcine using practice by the industry partner workers.The result of the voucer program is realization of a static router machine and skill acievement  by the industry partner workers in the machine operation. The static  router machine was made of right-angled  iron frame sizing 50x50x5 mm combined with steel plate of 3 mm thick. The machine is in 120x80x60 cm size moved by an electric motor power, SEM, of 0,5 HP and rotation  speed of2800   RPM.   The   machine   performance    and   productivity    especially    formanufacturing straight and curved, profiles for 9 mm size of meranti, kamper, and teak wood, is twice in speed as that of protable machines. If it is compared to that of manual profile planner, for manufacturing profiles with the same form and size, the router machine has five times in speed.Key words:   profile  machine,  small industry,  and wood furniture.